Phosphorus uptake mechanisms associated with phosphorus application levels in two cotton cultivars - Cai, Fangyuan; Zhang, Yingrong; Hou, Tianyu; Zhang, Man; Wang, Juanhong; Chen, Bolang (Frontiers in Environmental Science, 2023)
Poor phosphorus utilization is a common limitation of sustainable cotton production. Even so, the intrinsic potential for efficient phosphorus acquisition of the roots remains unclear. In this study, we aimed to explore if phosphorus acquisition in cotton is affected by interactions that could possibly be associated with root morphology and gene expression, between genotype and application rates. A pot experiment was conducted with seven phosphorus application rates: 0, 12.5, 25, 50, 75, 150, and 300 mg P kg−1. The agronomic characters, root morphology, and expression of the PHT1 gene in the roots of cotton varieties with different phosphorus acquisition efficiencies were measured. According to the results, the phosphorus acquisition efficiency in cultivar XLZ19 was higher than in XLZ13 for phosphorus uptake because of the upregulation of GhPTs gene expression that increased the total root length and proportion of fine roots. The Olsen-P levels in the soil ranged from 20 to 30 mg kg−1 at the seedling stage and from 15 to 25 mg kg−1 at the flowering stage, suggesting better root growth and phosphorus supply. The conversion of phosphorus fertilizers to soil Olsen-P decreased when the phosphorus application rate exceeded 50–75 mg kg−1. The phosphorus acquisition–efficient XLZ19 phenotype owes its efficiency to high GhPTs expression and morphological changes in the roots. Finally, with these crops that are highly efficient in phosphorus acquisition, agricultural practices in sustainable cotton production may consume less phosphorus fertilizers.